Foundations of Security Analysis and Design V FOSAD 2007/2008/2009 Tutorial Lectures - Aldini, Alessandro.; Barthe, Gilles.; Gorrieri, Roberto. (Lecture Notes in Computer Science, 2009)
FOSAD has been one of the foremost educational events established with the goal of disseminating knowledge in the critical area of security in computer systems and networks. Offering a good spectrum of current research in foundations of security, FOSAD also proposes panels dedicated to topical open problems, and giving presentations about ongoing work in the field, in order to favour discussions and novel scientific collaborations. This book presents thoroughly revised versions of ten tutorial lectures given by leading researchers during three International Schools on Foundations of Security Analysis and Design, FOSAD 2007/2008/2009, held in Bertinoro, Italy, in September 2007, August 2008, and August/September 2009. The topics covered in this book include cryptographic protocol analysis, program and resource certification, identity management and electronic voting, access and authorization control, wireless security, mobile code and communications security.